Islamic Law in Afghanistan: Islamization or Arabisation? - Haroun Rahimi (Indonesian Journal of Islamization Studies, 2026)
Afghanistan’s legal history is defined by persistent legal pluralism in which Hanafi Islamic law has continuously coexisted with customary norms (adat/Pashtunwali) and state legislation, rather than being replaced by a single imported legal model. This article examines whether the evolution of Islamic law in Afghanistan is best understood as an endogenous process of Islamization or as a form of Arabisation driven by external doctrinal, institutional, and political influences. It argues that Afghan legal development cannot be reduced to passive reception of Arab legal culture. Employing historical and doctrinal analysis, the article traces the embedding of Islam within Afghan legal culture, demonstrating that the authority of Sharia has long been grounded in local religious beliefs, customary practices, and the social legitimacy of religious elites. Simultaneously, Afghan Islamic legal thought has selectively engaged with transregional intellectual currents circulating across the Ottoman, Indian, and broader Pan-Islamic worlds. The article then examines critical moments of codification and constitutional development—from the Islamic legal modernism of the 1923 Constitution to subsequent constitutional regimes and contemporary Taliban governance to show how Afghan elites appropriated transnational Islamic discourses without fully displacing indigenous jurisprudential traditions. By analyzing tensions between Hanafi and Hanbali interpretations, Sufi and Salafi or Wahhabi orientations, and the dynamic interaction between Sharia and adat, the article contends that Afghanistan’s legal trajectory reflects a negotiated and locally grounded Islamization process. Arabised doctrinal imports are filtered, fragmented, and frequently subordinated to Afghan socio-ethnic realities. Conceptually, the article reframes Afghanistan as an active node of “juridical Pan-Islam,” highlighting Afghan agency in shaping Islamic law for state-building, modernization, and political authority.